The bone phenotype associated with cherubism is independent of Caspase-1-dependent inflammasome activation in the mouse - Badre-Victor Rabhi; Sylvie Thomasseau; Xavier Decrouy; Martine Cohen-Solal; Marcel Deckert; Amélie E. Coudert; François Brial (PLoS ONE, 2025)
Cherubism is a rare genetic disorder caused by SH3BP2 mutations. This sterile autoinflammatory disease is characterized by jaw osteolysis, in which bone tissue is replaced by multinucleated giant cells containing fibrous tissue. The cherubism mouse model (Sh3bp2 KI) is characterized by systemic bone loss as well as inflammatory phenotypes induced and maintained by TNFα. IL-1β, produced by the NRLP3 inflammasome through recruitment of Caspase-1, is involved in the development of sterile autoinflammatory disease. We previously reported a cherubism patient with elevated serum IL-1β, and cherubism mice also have elevated serum IL-1β levels. Thus, we wanted to disentangle the role of IL-1β in cherubism. To that end, we deleted Caspase-1 in Sh3bp2 KI mice to tamp down IL-1β production. However, deleting Caspase-1 did not rescue the systemic bone and inflammatory phenotypes.